SUN-003 Very Restricted Carbohydrate (Ketogenic) Diet: A Rare Cause of a Recurrent Hypoglycemic-Euglycemic Diabetic Ketoacidosis in the Pregnancy - Yaron, Marianna (J Endocr Soc, 2020)
Introduction: Although potential risk of DKA, ketogenic diet became popular among T1DM patients as proven to reduce the incidence of hypoglycemia, glycemic variability, and HbA1c (1). Severe carbohydrate restriction had not been included among DKA precipitating factors in pregnancy since a minimum consumption of 175 g of carbohydrates a day is recommended for pregnant women by the IOM and ADA. Proband: A 35-year-old pregnant woman (G2P1 at 29 weeks’ gestation) was admitted to the ICU because of a 12-hour history of severe nausea, 4 vomiting episodes (stomach contain), weakness, and metabolic acidosis accompanied by low normal BG values for pregnancy. She had a history of bulimia nervosa since 15 years of age that was well-controlled by severe carbohydrate restriction prior to pregnancy, and T1DM since 19 years of age. Her pre-pregnancy carbohydrate daily intake was ~ 20–30 g and BMI 24.1 kg/m(2). Good glycemic control was established before conception and continued until delivery. Upon admission, she was tachypneic and suffering from diffuse abdominal pain. Fetal monitoring and abdominal ultrasonography showed no significant changes, and the sonographic fetal weight was appropriate for gestational age. The laboratory results revealed metabolic acidosis pH 7.23, bicarbonate 11.7 mmol/L, anion gap 22.5, and BG 78 mg/dL. Lactate and salicylate blood levels were normal. The blood β-hydroxybutyrate was highly positive and the patient was diagnosed with euglycemic DKA. She was managed with a continuous intravenous insulin infusion and fluid and electrolytes repletion. The patient was discharged after three days of hospitalization only to return four days later because of the similar complaints with findings of blood β-hydroxybutyrate 7.7 mmol/L and BG levels of 61–65 mg/dL. Because of persistent ketonemia with low normal BG levels, patient was questioning about her dietary habits and revealed to maintain severe carbohydrate-restricted pre-conception eating manners. After repeated consultations by specialists for eating disorder, patient agreed to increase her carbohydrate intake to 120 gr per day. Fetal brain MRI, fetal heart and brain ultrasound were performed to evaluate potential negative effects of ketones, and all were found normal. No major malformations were observed in the newborn, and a normal growth pattern was observed at 5 months of age. Conclusion: This is the first report of a pregnant T1DM patient with long lasting bulimia nervosa excellently controlled by severe carbohydrate restriction prior pregnancy and occultly continued against medical advice through the pregnancy, causing repeatedly hypoglycemic-euglycemic DKA. References: 1. Schmidt S, Christensen MB, Serifovski N, et al. Low versus high carbohydrate diet in type 1 diabetes: A 12‐week randomized open‐label crossover study. Diabetes Obes Metab 2019; 21:1680- 1688